Facile ex situ formation of a LiF–polymer composite layer as an artificial SEI layer on Li metal by simple roll-press processing for carbonate electrolyte-based Li metal batteries. Issue 33 (11th August 2020) - Sun, Seho; Myung, Seungcheol; Kim, Gaeun; Lee, Dongsoo; Son, Hyunsu; Jang, Minchul; Park, Eunkyung; Son, Byoungkuk; Jung, Yeon-Gil; Paik, Ungyu; Song, Taeseup
Abstract : A facile and scalable process for the formation of artificial SEI layer is proposed by roll-press Li metal and fluoropolymer. The layer, composed of lithium fluoride and polymers, plays Li protection for highly stable lithium metal batteries. Abstract : Lithium (Li) metal is considered an ideal anode for next-generation Li metal batteries (LMBs). However, Li dendrite formation and low coulombic efficiency (CE) are major obstacles for its practical use in LMBs. The engineering of the interface between Li metal and electrolytes is crucial for better Li ion kinetics and interface stability to overcome the above problems. In this study, we report a thin LiF/defluorinated polymer (LiF@Po) composite as an artificial SEI layer. The LiF@Po composite layer, formed by a facile and scalable roll-pressing process using polytetrafluoroethylene (PTFE) and Li metal, is composed of an inner (lithium side) LiF-rich layer and an outer (electrolyte side) polymer rich (polyene/fluoropolymer) layer. The free space between LiF particles could be conformally filled with a polymeric layer, improving the Li surface coverage properties of the protection layer. This novel LiF@Po protection layer enables highly stable cyclability even in a carbonate-based electrolyte for more than 1000 h at 1 mA cm −2 in a Li‖Li symmetric cell and a cycle retention of 80% capacity for >200 cycles with an extremely stable average CE of 99.7% in a Li‖LiCoO2 full cell. Furthermore, this LiF@Po protection layer could significantly enhance the cyclability and reversible capacity in a Li‖LiNi0.8 Co0.1 Mn0.1 O2 (NCM-811) full cell.